2020
DOI: 10.1002/smll.202000656
|View full text |Cite
|
Sign up to set email alerts
|

Role of Redox‐Inactive Transition‐Metals in the Behavior of Cation‐Disordered Rocksalt Cathodes

Abstract: Owing to the capacity boost from oxygen redox activities, Li‐rich cation‐disordered rocksalts (LRCDRS) represent a new class of promising high‐energy Li‐ion battery cathode materials. Redox‐inactive transition‐metal (TM) cations, typically d0 TM, are essential in the formation of rocksalt phases, however, their role in electrochemical performance and cathode stability is largely unknown. In the present study, the effect of two d0 TM (Nb5+ and Ti4+) is systematically compared on the redox chemistry of Mn‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…[ 5,26 ] Using a combination of electrochemical characterization techniques, synchrotron X‐ray diffraction, soft and hard X‐ray absorption, resonant inelastic X‐ray scattering and differential electrochemical mass spectroscopy, previous studies have primarily attributed region A and B to the cationic Mn redox and anionic O redox, respectively, with the latter involving the oxidation of O 2− to O n − (0 < n < 2) and O 2 gas evolution. [ 15,26,30,41,42 ] The two regions are also indexed as A’ and B’ in the d Q/ d V plot (Figure 3b). Careful comparison shows that O redox activities in the B’ region tends to decrease with increasing F content in DRX, with the changes between F5 and F10 particularly significant.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5,26 ] Using a combination of electrochemical characterization techniques, synchrotron X‐ray diffraction, soft and hard X‐ray absorption, resonant inelastic X‐ray scattering and differential electrochemical mass spectroscopy, previous studies have primarily attributed region A and B to the cationic Mn redox and anionic O redox, respectively, with the latter involving the oxidation of O 2− to O n − (0 < n < 2) and O 2 gas evolution. [ 15,26,30,41,42 ] The two regions are also indexed as A’ and B’ in the d Q/ d V plot (Figure 3b). Careful comparison shows that O redox activities in the B’ region tends to decrease with increasing F content in DRX, with the changes between F5 and F10 particularly significant.…”
Section: Resultsmentioning
confidence: 99%
“…However, except for the densified layers (Figure 13b), the structure evolutions of DLROs are difficult to be detected due to their complex structural characteristics, which brings difficulties to mechanistic studies of voltage fade in DLROs. Kan et al 210 211 They found no obvious increase of Mn 2+ in discharged electrodes cycled five times compared to pristine when cycling within 1.5-4.2 V. However, when the upper cut-off voltage increased to 4.8 V, the amount of Mn 2+ increased with cycling, which suggest that the Mn reduction during cycling is induced owing to the anionic reactions above 4.2 V. Although the reduction of TM ions with cycling in anionic redox active DLROs has been profoundly observed 211,355 and should obviously be related to the voltage fade phenomena in DLROs. However, the intrinsic causes of the TM reduction and their detailed connection with electrochemical performances are rarely studied.…”
Section: Voltage Fade In Dlrosmentioning
confidence: 99%
“…Figure 3a shows the frequency with which several types of cation environments around F and Nb 5+ are both electrochemical inactive, they can affect atomic ordering and thus the percolating Li-content of DRX cathodes. 37,38 To rule out that the capacity improvement…”
Section: Computational Predictionsmentioning
confidence: 99%